A Highly Sensitive Electrochemical Sensor Based on Electrocatalytic Reduction Effect of Cu2+ on Trace Determination of Malathion in Soil and Other Complex Matrices - F. M. Alshareef; M. I. Orif; E. A. Al-Harbi; M. S. El-Shahawi (International Journal of Electrochemistry)
The current strategy reports a highly sensitive and selective square wave-cathodic stripping voltammetric protocol for malathion determination. The established method was based on the controlled adsorptive accumulation of malathion in the presence of Cu2+ ions in an aqueous solution of pH 2 onto the hanging mercury dropping electrode (HMDE) and measuring the resulting cathodic peak current of the adsorbed species at −0.42 V versus Ag/AgCl electrode. The low limits of detection (LOD) and quantification (LOQ) of malathion of the assay were estimated to be 3.1 × 10−10 and 1.03 × 10−9 M with a linear dynamic range of 1.03×10−9 – 2.0 × 10−7 M, respectively. The method was satisfactorily applied and validated for malathion determination in environmental samples. The experimental Student texp and Fexp values did not exceed the tabulated ttab (2.78) and Ftab (6.39) at 95% (P = 0.05) confidence (n = 5), confirming the precision and independence on the matrix. The developed sensing platform for the detection of malathion shows superior performance to conventional electrochemical methods. The proposed sensor offered simple, economical, reproducible, and applicable approach for the determination of malathion in environmental samples.